Mental Health Problems, Disability and Income Support Receipt: A Replication and Extension Using the HILDA Survey - Crosier, T; Rodgers, B; Butterworth, P (My University, 2004)
There is considerable evidence that social position and economic status are related to mental health. This article uses data from the first wave of the HILDA Survey to replicate and extend previous research demonstrating the elevated prevalence of mental disorders among different groups of Australian income support recipients. Welfare recipients were significantly more likely to experience moderate or severe disability due to poor mental health than non-recipients, with rates particularly elevated among clients receiving disability, lone parent and unemployment payments. To a large extent, these elevated rates of mental disability are consistent with the pattern of financial hardship and demographic characteristics such as gender and partnered status, and physical disability. However, a significant proportion of mental disability remains unexplained in several client segments. These findings have important implications for the design, delivery and evaluation of interventions to improve the social and economic participation of different welfare client groups.
Australian Journal of Labour Economics
Keywords: Benefits and Payments -- Income support; Health; Health -- Disability; Health -- Mental; Benefits and Payments; Health and wellbeing; Income, wealth and finances; Health; Benefits and Payments; Income support; Disability; Mental; Health and wellbeing; Income, wealth and finances